Kinetic and thermodynamic characterisation of HIV-protease inhibitors against E35D↑G↑S mutant in the South African HIV-1 subtype C protease. (1st January 2019) - Maseko, Sibusiso; Padayachee, Eden; Maphumulo, Siyabonga; Govender, Thavendran; Sayed, Yasien; Maguire, Glenn; Lin, Johnson; Naicker, Tricia; Baijnath, Sooraj; Gerhardus, Kruger Hendrik
Abstract: Herein, we report the effect of nine FDA approved protease inhibitor drugs against a new HIV-1 subtype C mutant protease, E35D↑G↑S. The mutant has five mutations, E35D, two insertions, position 36 (G and S), and D60E. Kinetics, inhibition constants, vitality, Gibbs free binding energies are reported. The variant showed a decreased affinity for substrate and low catalytic efficiency compared to the wild type. There was a significant decrease in the binding of seven FDA approved protease inhibitors against the mutant ( p < .0001). Amprenavir and ritonavir showed the least decrease, but still significant reduced activity in comparison to the wildtype (4 and 5 folds, respectively, p = .0021 and .003, respectively). Nelfinavir and atazanavir were the worst inhibitors against the variant as seen from the IC50, with values of 1401 ± 3.0 and 685 ± 3.0 nM, respectively. Thermodynamics data showed less favourable Gibbs free binding energies for the protease inhibitors to the mutant.